2016
DOI: 10.3855/jidc.6532
|View full text |Cite
|
Sign up to set email alerts
|

CD64 index on neutrophils can diagnose sepsis and predict 30-day survival in subjects after ventilator-associated pneumonia

Abstract: Introduction: Sepsis associated with ventilator-associated pneumonia (VAP) causes mortality in intensive care unit (ICU) patients. The time of diagnosis is crucial, and microbiological cultures take time. In this study, the diagnostic accuracy of CD64 index to predict VAP-induced sepsis and survival time in subjects requiring mechanical ventilation were evaluated and compared to conventional biomarkers and culturing methods. Methodology: A total of 32 subjects with VAP were included. Sepsis after VAP was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…Some biomarkers have been compared to PCT and CRP, most for their diagnostic value. A few were shown to be superior to PCT and/or CRP for this purpose, for example, presepsin and CD64 [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Some biomarkers have been compared to PCT and CRP, most for their diagnostic value. A few were shown to be superior to PCT and/or CRP for this purpose, for example, presepsin and CD64 [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that CD64 expression on neutrophils can be a useful diagnostic biomarker for both adult and neonatal sepsis , especially in combination with other biomarkers . Moreover, CD64 expression could serve as a potential early prognostic marker for sepsis as high levels of CD64 expression are closely related to both the severity and 28‐day mortality of sepsis .…”
Section: Alteration Of Neutrophil Function In Sepsismentioning
confidence: 99%
“…Some biomarkers have been compared to PCT and CRP, most for their diagnostic value. A few were shown to be superior to PCT and/or CRP for this purpose, for example, presepsin and CD64 [31][32][33].…”
Section: Discussionmentioning
confidence: 99%